Regional design: Discretionary approaches to regional planning in the Netherlands - Balz, Verena (A+BE | Architecture and the Built Environment, 2019)
In recent decades the Netherlands has seen an increase in the use of regional design-led practices in national indicative planning. Despite this, the interrelations between design and planning decision making are not well understood and attempts to involve the expertise and ambition of designers in planning have had unclear outcomes. This paper elaborates on the role and position of regional design in indicative planning. It is argued that design in this realm resembles discretionary action, implying that design both influences, and is influenced by, prevailing planning rationales. An analytical framework is developed on these grounds and applied to a set of regional design initiatives that evolved in the context of Dutch national plans between 1988 and 2012. Significantly, the analysis reveals forms of discretional control that shape the creative design practice, of particular importance being the flexibility of planning guidance and the resulting room for interpretation. In theoretical terms, the article contributes to the discussion of how design – as an explorative search for solutions to problems in a particular spatial context – and design theory can contribute to an understanding of the multiple planning experiments emerging in this post-regulative era.